Update on Chronic Hand Eczema (Canadian Dermatology Today, 2024)
Hand eczema is an inflammatory skin disease that often has a chronic course. Chronic hand eczema (CHE) is defined as eczema on the hands with a disease duration of longer than three months or two or more relapses per year. During the COVID-19 pandemic, hand eczema gained attention due to the increased risk of developing particularly irritant contact dermatitis in the context of a change in hand hygiene habits and frequency of hand washing.This has once more highlighted how important skin protection continues to be for prevention of the disease. Beyond this, new and updated guidelines are available, and a multitude of high-quality studies on hand eczema prevalence, pathogenesis and treatment have furthered our understanding of the disease and its management. This article aims to provide an overview on recent information about hand eczema with a focus on epidemiology, quality of life, and new treatment options.